Needs Analysis to Develop Heat E-Teaching Material Integrated Deep Learning and Local Wisdom to Facilitate Students' Creative Thinking Skills - Diah Hasna Azzahra; Asrizal Asrizal; Hidayati Hidayati; Fauziah Ulmi (Universitas Negeri Padang, 2026)
Effective physics learning requires digital instructional materials that are interactive, contextual, and capable of integrating local wisdom with a deep learning approach to support students’ creative thinking skills and conceptual understanding. However, heat instruction continues to face several challenges, including students’ low creative thinking skills, inadequate conceptual understanding, and the limited use of digital technology and local wisdom in existing teaching materials. These limitations contribute to suboptimal learning outcomes and reveal a gap between the competencies required for 21st-century education and the instructional resources currently used in schools. This study aims to analyze the need for developing digital teaching materials that integrate local wisdom with a deep learning approach to facilitate students’ creative thinking skills. A mixed-methods approach was employed, with data collected through questionnaires, creative thinking skill tests, and analyses of students’ learning outcome documents. The findings indicate that such digital teaching materials have the potential to increase students’ learning motivation, active participation, creative thinking skills, and conceptual understanding of physics concepts. Therefore, integrating local wisdom and deep learning into digital teaching materials represents an innovative strategy for improving physics instruction while addressing students’ learning needs and supporting the development of competencies required in the 21st century.